The influence of high-latitude flux lobes on the Holocene paleomagnetic record of IODP Site U1305 and the northern North Atlantic - Stoner, Joseph S.; Channell, James E. T.; Mazaud, Alain; Strano, Sarah E.; Xuan, Chuang (Geochemistry, Geophysics, Geosystems, 2013)
Paleomagnetic analysis and radiocarbon dating of an expanded Holocene deep-sea sediment sequence recovered by Integrated Ocean Drilling Program (IODP) Expedition 303 from Labrador Sea Site U1305 (Lat.: 57 degrees 28.5 N, Long.: 48 degrees 31.8 W, water depth 3459 m) provides insights into mechanisms that drive both paleomagnetic secular variation (PSV) and magnetization acquisition in deep-sea sediments. Seventeen radiocarbon dates on planktonic foraminifera define postglacial (ca. 8 ka) sedimentation rates as ranging from 35 to > 90 cm/kyr. Alternating field (AF) demagnetization of u-channel samples show that these homogeneous sediments preserve a strong, stable, and consistently well-defined component magnetization. Normalized remanence records pass reliability criteria for relative paleointensity (RPI) estimates. Assuming that the age of magnetization is most accurately defined by well dated PSV records with the highest sedimentation rates, allows us to estimate and correct for temporal offsets at Site U1305 interpreted to result from postdepositional remanence acquisition at a depth of similar to 20 cm. Comparisons indicate that the northern North Atlantic PSV and RPI records are more consistent with European than North American records, and the evolution of virtual geomagnetic poles (VGP) are temporally and longitudinally similar to global reconstructions, though with much larger latitudinal variation. The largest deviations from a geocentric axial dipole (GAD) are observed during times of the highest intensities, in contrast to the usual assumption. These observations are consistent with the idea that PSV in the North Atlantic and elsewhere during the Holocene results from temporal oscillations of high-latitude flux concentrations at a few recurrent locations.